Specifika russkih otglagol'nyh imen suščestvitel'nyh proizvodstvenno-tehničeskoj leksiki : slovoobrazovatel'nyj i leksiko-semantičeskij analiz - Valtakari, Pertti (1991)
The research aims at g1vшg а qualitative-quantitive description of the word formation and lexical-semantic characteristics of verbal nouns in Russian technical words. The research gives an overall picture; it investigates general technical vocabulary as well as special terms in different fields of technology. The study is based оn motivating verbs, in the analysis of which the main attention has been paid to conjunction, aspect, word changing, formation method, word roots, prefixes, transitivity/intransitivity, semantic type, word formation mechanism and special cases. This is followed bу а lexical-semantic analysis of verbal nouns, in which primary and secondary word formation semantics are clarified, from their semantic subtypes to their general semantics. The relationship of verbal nouns and motivating verbs (subject, object, instrument, result/product, and place) has also been taken into account in the analysis. Non-productive models have been included in addition to productive word formation models. The source material is mainly based on unilingual and multilingual technical dictionaries and reference books which give а balanced, diverse and systematic range of information on many different fields of technology. The research introduces new detailed information leading to а more complete qualitative-quantative description of Russian verbal nouns - their formation, semantics, synonyms, and their motivating verbs.